Strong Convergence of A Hybrid Method for Infinite Family of Nonexpansive Mapping and Variational Inequality - Rathee, Savita; Swami, Monika (IndoMS, 2021)
The motivation behind this paper is to use hybrid method for searching a typical component of the set of fixed point of an infinite family of non expansive mapping and the set of monotone, Lipschtiz continuous variational inequality problem. The contemplated method is combination of two method one is extragradient method and the other one is DQ method. Also, we demonstrate the strong convergence of the designed iterative technique, under some warm conditions.